A cost-based approach for evaluating the impact of a network of distributed energy systems on the centralized energy supply. Issue 1 (February 2020) - Fichera, Alberto; Frasca, Mattia; Volpe, Rosaria
According to the Fifth Assessment Report of the International Panel on Climate Change, cities account for the 67% of the global energy demand and are the major contributors in emitting CO2 in the atmosphere. To face this problem, National and European policies pushes towards the insertion of distributed energy systems within urban areas as a valid alternative to the traditional centralized energy supply. In this direction, the installation of distributed energy systems gives raise to consumers with production capabilities, by now called 'prosumers'. They use the autonomously produced energy to satisfy their own energy requirements and distribute the eventual exceed to neighbours. Yet, the energy exchanges occurring among prosumers permit the modelling of a network where nodes are identified as the prosumers and the energy interactions as links. This paper deals with this issue and proposes a cost-based methodology to model the energy distribution network of prosumers within the urban territories by deepening their impact on the traditional supply. Results are discussed by comparing a theoretical energy distribution network to a real case study.